ANALYSIS IN GENOTYPES OF INDIAN MUSTARD (Brassica juncea Brassica juncea L. czern & coss) L. czern & coss - GREESH KUMAR SINGH; YOGESH PANDEY; LOKENDRA SINGH (The Bioscan, 2024)
The present investigation comprised of seven strains / varieties and their twenty one F1 crosses developed in a diallel mating design was carried out for evaluation of eleven characters viz. Days to flowering, days to maturity, plant height, length of main raceme, number of siliquae/ plant, number of seeds/ siliqua, number of primary branches/ plant, number of secondary branches/ plant, 1000 seed weight, oil content and seed yield/ plant. Analysis of variance revealed significant differences among the genotypes for all the characters. In general, PCV was higher than GCV for almost all the characters. High heritability coupled with genetic advance over mean was observed for test weight. In general, genotypic correlation coefficients were higher than phenotypic ones for all the traits, indicating environmental influence on the expression of these traits. Seed yield per plant had positive correlation with number of siliquae per plant, test weight while seed yield per plant had negative association with number of primary branches per plant both at genotypic and phenotypic levels. Highest direct effect was obtained by number of secondary branches per plant followed by day to maturity, test weight and oil content on seed yield.